The Role of Geography, Diet, and Host Phylogeny on the Gut Microbiome in the Hawaiian Honeycreeper Radiation - Maria S. Costantini; Elin Videvall; Jeffrey T. Foster; Matthew C. I. Medeiros; John D. Gillece; Eben H. Paxton; Lisa H. Crampton; Hanna L. Mounce; Alex X. Wang; Robert C. Fleischer; Michael G. Campana; Floyd A. Reed (Ecology and Evolution)
ABSTRACT The animal gut microbiome can have a strong influence on the health, fitness, and behavior of its hosts. The composition of the gut microbial community can be influenced by factors such as diet, environment, and evolutionary history (phylosymbiosis). However, the relative influence of these factors is unknown in most bird species. Furthermore, phylosymbiosis studies have largely focused on clades that diverged tens of millions of years ago, and little is known about the degree of gut microbiome divergence in more recent species radiations. This study explores the drivers of microbiome variation across the unique and recent Hawaiian honeycreeper radiation (Fringillidae: Drepanidinae). Fecal samples were collected from 14 extant species spanning the main islands of the Hawaiian archipelago and were sequenced using three metabarcoding markers to characterize the gut microbiome, invertebrate diet, and plant diet of Hawaiian honeycreepers. We then used these metabarcoding data and the honeycreeper host phylogeny to evaluate their relative roles in shaping the gut microbiome. Microbiome variation across birds was highly individualized; however, source island had a small but significant effect on microbiome structure. The microbiomes did not recapitulate the host phylogenetic tree, indicating that evolutionary history does not strongly influence microbiome structure in the honeycreeper clade. These results expand our understanding of the roles of diet, geography, and phylogeny on avian microbiome structure, while also providing important ecological information about the diet and gut microbiota of wild Hawaiian honeycreepers.